KAJIAN VISUAL KOMPOSISI FOTOGRAFI DALAM FOTO KOMERSIAL HARPER’S BAZAAR - Liana Fallah; Maya Purnama Sari (Narada : Jurnal Desain dan Seni, 2022)
Photography is basically a medium for documenting moments that you want to remember and are usually important. The large number of enthusiasts in the field of photography and the increasingly advanced developments of the times have made the scope of this photography wider, not just documentation but also reaching the industrial world for commercial needs so that it is called commercial photography. Commercial photography, especially fashion photography, is something that many people love. Harper's Bazaar is a fashion magazine that uses commercial photography to promote fashion products. In commercial photography, of course, there is a photographic composition that is used, therefore the authors formulate a goal to conduct research on the composition applied to the commercial photography of Harper's Bazaar magazine "California Dreaming". By using qualitative methods and analysis by studying commercial photography directly. Then it is explained one by one regarding the photographic composition used so as to produce conclusions about the photography studied. Where from the research results it was found that each photo has its own photographic composition, with such an arrangement that finally the point of interest in a photo can be highlighted.